School Health: Pediatric Primary Care Curriculum - Lauren R. Anderson; Cheryl Yang; Jillian Mayer Cotter; Christina Baker; Pamela Brunner Nii; Colette Christen; Mandy Allison; Daniel Nicklas (Association of American Medical Colleges, 2018)
Introduction Pediatric residents encounter issues related to school health (SH) throughout their training, particularly in their continuity clinics, and often serve as liaisons between a patient's medical home and school environment. However, there is currently a paucity of formal education on SH for pediatric residents to prepare them for this role. Methods We created a 3-hour interactive learning conference that was delivered to four groups of six to eight pediatric residents during their intern year by a multidisciplinary team. Our curriculum focused on understanding the differences between individualized educational plans (IEPs), individualized health plans (IHPs), and 504 plans; the IEP process; and communication with schools. Residents were given pre- and postdidactic surveys, completed reflective writings, and participated in feedback sessions. Results Twenty-seven pediatric interns completed the curriculum; 85% and 74% had improved knowledge of IEP/504/IHP and SH personnel, respectively. Eighty-five percent reported feeling comfortable with family conversations about accommodations postcurriculum versus 0% precurriculum. The majority of interns found the curriculum to be valuable to their clinic performance. Discussion Our curriculum offers a unique multidisciplinary approach to teaching and can be easily integrated into other residency programs, even with limited protected didactic time.